WACANA HAK-HAK ATAS KEKAYAAN INTELEKTUAL DALAM PENCIPTAAN KARYA DESAIN GRAFIS - S. Banindro, Baskoro (Institute of Research and Community Outreach - Petra Christian University, 2002)
Graphic design product is produced by many creative process after many lay out%2C have been made comprehensively. While producing design%2C graphic designer usually have their own style. Style that is produced by graphic designer is an intellectual property product that must be protected. In other way%2C the right of intellectual property as a law product%2C trying to protect the creation of graphic designer throught the law of mark and copy right. Abstract in Bahasa Indonesia : Karya desain grafis pada hakekatnya merupakan buah pikir dari serangkaian proses kreatif setelah melalui beberapa tahap layout secara komprehensif. Karya desain biasanya identik dengan style seseorang dalam menghasilkan karya%2C yang tidak lain merupakan produk kekayaan intelektual desainer yang patut untuk dilindungi. Hak-hak atas kekayaan intelektual sebagai produk hukum disisi lain berupaya melindungi produk grafis atas penciptaan seorang desainer melalui perangkat UU Hak Cipta dan Merek. Intelectual property right%2C graphic design%2C law of mark and copy right.